On the performance of open-loop transmit diversity techniques for IS-2000 systems a comparative study. - Soni, R.A (IEEE Transactions on wireless communications)
Third-generation code-division multiple access (CDMA) cellular systems incorporate a downlink transmission technique called transmit diversity (TD). This paper provides a comprehensive investigation of the performance and practical implementation issues of open-loop transmit diversity schemes for the IS-2000 third-generation cellular CDMA standard. Discussed in detail are orthogonal transmit diversity (OTD) and space-time spreading (STS) diversity schemes. STS is a TD technique that is motivated by space-time coding principles originally described for narrowband systems. OTD is a TD technique that obtains diversity not at the symbol level, but in the decoding process, and has performance that is in general lower bounded by STS, which obtains diversity combining prior to decoding. Thus, STS always outperforms OTD, with the improvement particularly significant in the presence of weak convolutional codes. Probability of error analysis is performed for STS under the assumptions of imperfect channel estimates, correlation between antennas, and unequal pilot power allocations. Extensions to STS are provided for the multicarrier version of the standard and four transmit antennas. Simulation studies are performed to detail the performance of both open-loop TD schemes with convolutional coding and closed-loop power control consistent with the 3GPP2/IS-2000 standard. Many of these results were generated in the course of the IS-2000 standardization procedure. Performance is studied in radio environments which experience flat Rayleigh fading, frequency selective Rayleigh fading, spatially selective fading, as well as Ricean fading with various K factors. Some additional results are presented for cases where mobile receivers have two receive antennas. Implementation issues are also considered including the impact of antenna delay differences on performance, transmitter and receiver architectures, and computational complexity.